2017
DOI: 10.3758/s13414-017-1364-z
|View full text |Cite
|
Sign up to set email alerts
|

Facial race and sex cues have a comparable influence on emotion recognition in Chinese and Australian participants

Abstract: The magnitude of the happy categorisation advantage, the faster recognition of happiness than negative expressions, is influenced by facial race and sex cues. Previous studies have investigated these relationships using racial outgroups stereotypically associated with physical threat in predominantly Caucasian samples. To determine whether these influences generalise to stimuli representing other ethnic groups and to participants of different ethnicities, Caucasian Australian (Experiments 1 and 2) and Chinese … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 39 publications
3
14
0
Order By: Relevance
“…As mentioned above, previous studies of the effect of social category cues on emotion perception cannot completely rule out stimulus artifacts as the faces used are evaluated more or less positively based on interpretation of facial cues. For instance, it is possible that the way females express emotions differs from males or that structural differences between female and male, or own- and other-race faces introduce the observed bias in emotion perception (although see Craig, Koch, & Lipp, 2017; Craig, Zhang, & Lipp, 2017; Lipp et al, 2015). In the present study, the same faces were manipulated to be evaluated positively or negatively across participants and we demonstrate for the first time that the influence of evaluations on emotion recognition is independent of the unique qualities of the face.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned above, previous studies of the effect of social category cues on emotion perception cannot completely rule out stimulus artifacts as the faces used are evaluated more or less positively based on interpretation of facial cues. For instance, it is possible that the way females express emotions differs from males or that structural differences between female and male, or own- and other-race faces introduce the observed bias in emotion perception (although see Craig, Koch, & Lipp, 2017; Craig, Zhang, & Lipp, 2017; Lipp et al, 2015). In the present study, the same faces were manipulated to be evaluated positively or negatively across participants and we demonstrate for the first time that the influence of evaluations on emotion recognition is independent of the unique qualities of the face.…”
Section: Discussionmentioning
confidence: 99%
“…Invariant facial cues, such as sex and race, have been shown to moderate the happy face advantage. The happy face advantage has been shown to be larger for female faces when categorized together with male faces (Bijlstra, Holland, & Wigboldus, 2010; Craig, Koch, & Lipp, 2017; Craig & Lipp, 2017; Craig, Zhang, & Lipp, 2017; Hugenberg & Sczesny, 2006; Lipp, Craig, & Dat, 2015; Lipp, Karnadewi, Craig, & Cronin, 2015), and is sometimes reversed for the male faces, with angry expressions being recognized faster (Becker, Kenrick, Neuberg, Blackwell, & Smith, 2007). Conversely, the happy face advantage is evident for male own-race faces when categorized together with male other-race faces (Bijlstra et al, 2010; Craig, Koch, et al, 2017; Craig, Mallan, & Lipp, 2012; Lipp, Craig, et al, 2015), and sometimes a reversed pattern has been observed on the male other-race faces, where the negative expression has been categorized faster than happy expressions (Craig et al, 2012; Hugenberg, 2005).…”
mentioning
confidence: 99%
“…Cultural issues must be taken into account when understanding these emotional expressions, as they can exert an influence on their recognition 73 . A study that considered ethnicity as an influencing factor in the performance of emotion recognition tasks and compared this ability to identify emotions between Australian and Chinese individuals verified that people perform worse when classifying emotions that are expressed on faces of another ethnicity 74 . In this sense, the cultural characteristics of the stimulus presented can also modulate performance in the test.…”
Section: Discussionmentioning
confidence: 99%